Very fast moving radar echoes as observed CPS-9 Radar (MAUSAM, 1961)
In this study, a few instances of very rapidly moving radar echoes, as observed on the CPS-9 Radar at Safdarjung (New Delhi), are presented and discussed in the light of available observations and existing theories.  It has been shown that these echoes-apparently moving at speeds of more than 200 mph-cannot be due to radar returns from aircrafts or from birds.  It has been concluded that these were in fact cases of radarscope misinterpretation; the radar beam at each successive rotation encountering a different blob in almost the same azimuth and range, and thus giving the impression that the successive echoes were due to the same radar object flying across the scope at a terrific speed of hundreds of miles per hour.